Validity of fecal coliforms, total coliforms, and fecal streptococci as indicators of viruses in chlorinated primary sewage effluents. - Berg, G (1978)
Quantities of combined chlorine that usually destroyed more than 99.999% of the indigenous fecal coliforms, total coliforms, and fecal streptococci in primary sewage effluents destroyed only 85 to 99% of the indigenous viruses present. Viruses were recovered from five of eight chlorinated primary effluents from which fecal coliforms were not recovered by standard most-probable-number procedures. The limited volumes of such chlorinated effluents that can be tested for indicator bacteria with currently available multiple-tube and membrane filter techniques restrict the value of fecal coliforms, fecal streptococci, and even total coliforms as indicators of viruses in these effluents. Although fecal coliforms and fecal streptococci are useful indicators of viruses in effluents from which these bacteria are recovered, the absence of these bacteria and even total coliforms from disinfected effluents (in standard tests) does not assure that viruses are also absent.